1917 AND THE CONSEQUENCES (London)
1 online resource.
Keywords: The Russian Revolution of 1917 has been one of the most important events of modern history. It changed the course of the events not only in Russia but, on a wider scale, across the world while it influenced the flow of history throughout the twentieth century until the fall of the Soviet Union and, to some extent, well beyond this time. Radical change in Russia triggered social revolutions and reformations across Europe, while authoritarian systems shaped their societies according to the Russian model. This book analyses these forces, particularly at the European periphery which has been underexplored until this volume.